An Evaluation System of Policy Alternatives Based on TRANUS from The Viewpoint of A Compact City - Miyamoto, Kazuaki; Vichiensan, Varameth; Roychansyah, Muhammad Sani; Sato, Yukiya (2003)
Attached in complete paper